Fundamentals of Pediatric Surgery - Mattei, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The first two editions of Fundamentals of Pediatric Surgery (2011, 2017) were meant to be comprehensive, state-of-the-art, and practical. The 3rd edition builds on this commitment to such time-honored principles with a text that is even more wide-ranging in its content. It has a deeper commitment to relying on the most current scientific evidence, provides additional study materials to aid in comprehension of concepts and for more effective preparation for oral and written examinations, and be accessible through a variety of multimedia platforms for busy surgeons who have less and less time to sit and read a text but who need to understand this important material while on call, on the go, or between cases. The book maintains its easy-to-read, (3z(Bthis is how I do it(3y (Bstyle of writing. Each chapter is written by an eminent expert in the field, supplemented with illustrations and photographs that bring the material to life. Each is also enhanced with editor$1 (Bs comments, suggested readings and references, case studies, and sample questions. The book is available in a high-quality digital version. To further supplement the learning experience for readers who purchase the text, videos, interviews, and lectures are available on-line. This text will continue to be the most comprehensive, up-to-date, and easily accessible pediatric surgery text of its kind, written in a concise and direct style that covers indications, alternatives, anticipated benefits, and potential pitfalls of every pediatric surgical condition and operation and supported by the latest research published in the current literature.s
Part I - Perioperative Care -- Preoperative Assessment and Preparation -- Prenatal Diagnosis and Genetic Counseling -- Neuraxial & Regional Anesthesia -- Incisions and Positioning -- Enteral Nutrition and Access -- Parenteral Nutrition -- Enhanced Recovery after Surgery Protocols (ERAS) - The Next Generation of Perioperative Quality Improvement, Safety and Innovation -- Quality Improvement in Pediatric Surgery -- Part II - Critical Care -- Fetal Intervention -- Shock -- Electrolyte Abnormalities -- Coagulopathy and Transfusion Medicine -- Vascular Access -- Acute Kidney Injury -- Mechanical Ventilation -- Extracorporeal Life Support (ECMO) -- Part III - Trauma -- Trauma Resuscitation -- Pediatric Head Injury -- Concussion -- Neck Injuries -- Spinal Column and Spinal Cord Injuries -- Burns -- Abdominal Trauma -- Thoracic Trauma -- Vascular and Extremity Injuries -- Pediatric Hand Injuries -- Child Physical Abuse -- Part IV - Head and Neck -- The Critical Airway -- Bronchoscopy and Airway Disorders -- Benign Neck Masses -- Thyroid and Parathyroid Disease -- Part V - Skin and Soft Issues -- Benign Skin Lesions -- Hemangiomas and Vascular Malformations -- Disorders of the Breast -- Necrotizing Soft Tissue Infections -- Pilonidal Disease -- Lymphatic flow disorders -- Palmar Hyperhidrosis -- Part VI - Thorax and Mediastinum -- Complex Wound Management -- Lung Biopsy and Resection -- Diseases of the Pleura -- Congenital Lung Lesions -- Patent Ductus Arteriosus -- Vascular Compression Syndromes -- Pectus Deformities -- Mediastinal Masses -- Esophageal Atresia -- Long-Gap Esophageal Atresia -- Lesions, Injuries and Replacement of the Esophagus -- Part VII - Stomach and Small Intestines -- Foregut Duplications -- Achalasia -- Gastroesophageal Reflux Disease and Hiatal Hernia -- The Stomach -- Congenital Duodenal Obstruction -- Intestinal Atresia -- Abdominal Cysts and Duplications -- Intestinal Rotational Anomalies -- Necrotizing Enterocolitis -- Intestinal Failure and Rehabilitation -- Meconium Ileus -- Intussusception -- Meckel$1 (Bs Diverticulum -- Bariatric Surgery -- Chronic Abdominal Pain -- Crohn$1 (Bs Disease -- Ileostomy and Colostomy -- Small Bowel Obstruction -- The Small Intestine -- Gastrointestinal Bleeding -- Enterocutaneous Fistula -- Part VIII - Colon, Rectum and Anus -- Constipation and Fecal Incontinence -- Hirschsprung Disease -- Perianal Disease -- Appendicitis -- Ulcerative Colitis and Familial Polyposis -- Anorectal Malformations -- Part IX - Abdominal Wall, Peritoneum and Diaphragm -- Gastroschisis -- Omphalocele -- Eventration of Diaphragm -- Congenital Diaphragmatic Hernia -- Inguinal Hernia -- Uncommon Hernias -- Hernia and Disorders of the Umbilicus -- Peritoneal Dialysis -- Ventricular Shunts for Hydrocephalus -- Disorders of the Abdominal Aorta and Major Branches -- Part X - Liver, Biliary Tree, Pancreas and Spleen -- Neonatal Hyperbilirubinemia -- Biliary Atresia -- Congenital Intrahepatic Cholestasis -- Gallstones and Cholecystitis -- Choledochal Cyst -- Benign Liver Lesions -- Hepatic Resection -- Portal Hypertension -- Total Pancreatectomy with Islet Autotransplantation -- Congenital Hyperinsulinism -- Pancreatitis -- The Pancreas -- Surgical Disorders of the Spleen -- Part XI - Genitourinary -- Vesicoureteral Reflux -- Neurogenic Bladder and Bladder Augmentation -- Penile Anomalies and Circumcision -- Undescended Testes -- The Acute Scrotum -- Bladder and Cloacal Exstrophy -- Differences in Sex Development -- Disorders of the Vagina -- Benign Disorders of the Adnexa -- Part XII - Surgical Oncology -- Pediatric Surgical Oncology -- Neuroblastoma -- Adrenal Tumors and Pheochromocytoma -- Wilms Tumor -- Liver Tumors -- Rhabdomyosarcoma -- Non-rhabdomyosarcoma Soft-Tissue Sarcoma -- Chest Wall Tumors -- Sacrococcygeal Teratoma -- Ovarian Tumors -- Testicular Tumors -- Melanoma and Atypical Nevi -- Musculoskeletal Tumors -- Uncommon Malignancies -- Inflammatory Myofibroblastic Tumors and Pseudotumors -- Pediatric Fertility Preservation.s
Keywords: Children$1 (BSurgery.s; Surgery; Nursing; Pediatric Surgery; Surgery; Nursing; Surgical Procedures, Operative; Child; Infant